Ettore Majorana : unpublished research notes on theoretical physics - Ghirardi, Giancarlo ; Petkov, Vesselin ; Sudbery, Tony ; Merwe, Alwyn ; Esposito, Salvatore ; Recami, Erasmo ; Merwe, Alwyn ; Battiston, Roberto (Springer, 2017)
496 p.